重要极限:
$\lim\limits_{x\rightarrow \infty}(1+\frac{1}{x})^x=\lim\limits_{x\rightarrow 0}(1+x)^{\frac{1}{x}}=e $,这个做对数导数的时候经常用到。

举个例子:

$[\text{ln}(x)]'=\frac{\text{ln}(x+\Delta x)-\text{ln}~x}{\Delta x}=\text{ln}(1+\frac{\Delta x}{x})^{\frac{1}{\Delta x}}=\text{ln}[(1+\frac{\Delta x}{x})^{\frac{x}{\Delta x}}]^{\frac{1}{x}}=\text{ln}e^{\frac{1}{x}}=\frac{1}{x}$

接下来主要证明$(x^n)'=nx^{n-1}$。

首先要证明三个极限:

  1. $\lim\limits_{a\rightarrow 0}\frac{\log_a(1+a)}{a}=\log_a e$

$\lim\limits_{a\rightarrow 0}\frac{\log_a(1+a)}{a}=\lim\limits_{a\rightarrow 0}\log_a(1+a)^{\frac{1}{a}}=\log_a e$

  1. $\lim\limits_{n\rightarrow 0} \frac{a^n -1}{n}=\ln a$

令$m=a^n -1$,则$n=\log_a(m+1)$。

由于$n \rightarrow 0$,则$a^n\rightarrow a^0 =1$,$m=a^n -1 \rightarrow 0$。

原式=$\lim\limits_{m\rightarrow 0}\frac{m}{\log_a(m+1)}=\frac{1}{\log_ae}=\frac{1}{\frac{\ln e}{\ln a}}=\ln a$

  1. $\lim\limits_{a\rightarrow 0}\frac{(1+a)^n-1}{a}=n$

令$\beta=(1+a)^n-1$,由于$a\rightarrow 0$,$\beta\rightarrow(1+0)^n-1=0$,

又$n\ln(1+a)=\ln(\beta +1)$,

于是$\lim\limits_{a\rightarrow 0}\frac{(1+a)^n-1}{a}=\lim\limits_{a\rightarrow 0}\frac{\beta}{\ln(1+\beta)}*n\frac{\ln(1+a)}{a}=\lim\limits_{\beta\rightarrow 0}\frac{\beta}{\ln(1+\beta)}*n\lim\limits_{a\rightarrow 0}\frac{\ln(1+a)}{a}=n$

开始证明$(x^n)'=nx^{n-1}$:

$\begin{aligned}\frac{(x+\Delta x)^n-x^n}{\Delta x}&=\frac{(x(1+\frac{\Delta x}{x}))^n-x^n}{\Delta x}\\&=\frac{x^n(1+\frac{\Delta x}{x})^n-x^n}{\Delta x}\\&=\frac{x^n[(1+\frac{\Delta x}{x})^n-1]}{\Delta x}\\&=\frac{x^{n-1}[(1+\frac{\Delta x}{x})^n-1]}{\frac{\Delta x}{x}}\end{aligned}$

根据极限$3$,原式$=nx^{n-1}$

证毕。